Tn = a + (n-1)d
when n = 12, tn = 63
63 = a + (12-1)*5
a = 63 - 55 =8
tn or an
= 8 + (n-1) 5
= 3 + 5n
Hope this helps
Answer:5
Step-by-step explanation:
If you look at the question in reverse you can backtrack your way through. Take 10 and instead of dividing, multiply it by 10, which is 60, add 6 instead of subtracting, which is 66, divide by 6 instead of multiplying, which is 11 and finally subtract 6 instead of adding, which is 5. Use five and try the question over to make sure you calculated correct.